1999
DOI: 10.1520/gtj11311j
|View full text |Cite
|
Sign up to set email alerts
|

Cell Size for Water Content-Dielectric Constant Calibrations for Time Domain Reflectometry

Abstract: Time domain reflectometry (TDR) is a nondestructive electromagnetic technique used to measure the volumetric water content of soil. A key component of the method is the calibration equation relating the apparent dielectric constant (Ka) to the volumetric water content (ϑ). In this study, tests were conducted to evaluate dimensional requirements for a TDR calibration cell. The results show that a PVC cylinder having the same dimensions as a standard compaction mold (diameter = 102 mm, height = 116 mm) is a suit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The unbound granular material was compacted within the calibration box in two horizontal layers. The electromagnetic field around the sensor did not exceed 30 mm (18), which is smaller than the distance of the outer rod to the wall of the box.…”
Section: Calibration Boxmentioning
confidence: 89%
“…The unbound granular material was compacted within the calibration box in two horizontal layers. The electromagnetic field around the sensor did not exceed 30 mm (18), which is smaller than the distance of the outer rod to the wall of the box.…”
Section: Calibration Boxmentioning
confidence: 89%
“…Figure 3 shows the calibration box (with inner dimensions of 16.2 × 18.2 × 20.1 cm 3 ) and the procedure used to establish the relationship between the sensor output (mA) and volumetric water content (θ = V w /V, where V w is the volume of water and V is the total volume of soil). This specific size of the calibration box was chosen to minimize boundary effects on the moisture sensor signal, as suggested by Suwansawat et al [18]. To replicate field conditions as closely as possible, the soil sample was re-compacted in the calibration box to achieve the same dry unit weight as that of an undisturbed sample.…”
Section: Laboratory Testing Of Soilmentioning
confidence: 99%
“…It can be found that when the rod lengths are 10 cm, 15 cm, and 20 cm, the errors of h will be 0.8 %, 0.5 %, and 0.4 %, respectively. On the other hand, Suwansawat and Benson (1999) indicated that increasing of the rod length may lead to greater loss and attenuation of the TDR signal. Therefore, 15 cm is chosen as the length of the rods into the soil.…”
Section: Design Of the Rodsmentioning
confidence: 99%